Exploring the Strategic Role of Higher Education in Human Resource Development in Education: A Qualitative Case Study of Tribhuvan University - Mainali, Bhawani Prasad (Curriculum Development Journal, 2025)
The purpose of this study is to explore how Tribhuvan University, Faculty of Education, uses its academic programs, policies and strategic initiatives to support the development of qualified human resources in the education system of Nepal. The study employed a qualitative case study research design to conduct an empirical investigation, involving the participation of assistant dean, chairs of subject committee; department heads and students from Mahendra Ratna Campus, Tahachal. The results show that The Faculty of Education should prioritize pedagogy-based Bachelor's and Master's degrees with career assurances and regular monitoring mechanisms, it faces challenges in human resource development due to inconsistent affiliation licenses, students and teachers are dissatisfied with the Faculty of Education's policies and programs, which fail to consider their needs and socioeconomic backgrounds, leading to poor implementation and low pass rates, and it is urged to improve policy implementation by empowering subject committees, aligning curricula with market demands, prioritizing pedagogy-based degrees. The Faculty of Education is crucial in matching its academic programs with the demands of the country in terms of human resource development, but there is still room for improvement in a few areas, including infrastructure, curriculum updates, and closer ties between theoretical knowledge and real-world application. TU Faculty of Education is crucial to producing a trained workforce that can fulfill Nepal's changing educational needs and promote the nation's socioeconomic development.